Gestão coletiva de bens comuns: possibilidades para o parque nacional da serra da canastra - MG - Prado, Michella Christian do (2020)
In this dissertation, the understanding that they have about the rules for the management of the Serra da Canastra National Park is investigated from the perspective of the actors involved. In this sense, the research question was: What are the possibilities and alternatives for effective collective and cooperative management in the Serra da Canastra National Park, Minas Gerais? The general objective was to analyze the possibilities and alternatives for effective collective and cooperative management in the Serra da Canastra National Park, Minas Gerais. Specifically, the intention was to: a) Identify the actors involved in the management of the Serra da Canastra National Park; b) Describe the existing conflicts and institutional arrangements that involve the management of the Serra da Canastra National Park; c) Analyze the principles of collective management present and absent in the management of the Serra da Canastra National Park; and d) Present alternatives for collective management for the Serra da Canastra National Park. We discussed the collective management of common assets, which is particularly important when it comes to analyzing natural assets. Several authors have dedicated themselves to the study of this theme, however, the theoretical north of the study was the work of Elinor Ostrom. The research methodology is qualitative and descriptive. The PNSC covers six municipalities in the state of Minas Gerais: Capitólio, Delfinópolis, Sacramento, São João Batista do Glória, São Roque de Minas and Vargem Bonita and its administration is headquartered in the municipality of São Roque de Minas. Data were collected through interviews, documentary research and observation. The results were analyzed using the theoretical categories of Ostrom (1990), namely: well-defined borders; consistency between the rules of appropriation and provision with local conditions; collective decision arrangements; monitoring users and resources; gradual sanctions; conflict resolution mechanisms; minimal recognition of organizational rights; and intersectoral alignment and articulation in management. In all theoretical categories, limitations were found for collective management of common resources, however, it was observed that the current management of the PNSC has sought to approach the different actors and provided an expansion in the possibilities of collective management. It is known that managing is a process and the objective of establishing collective management is a pedagogical process that requires the awareness of those involved because it is a specific and specific management because it is about managing a common good whose property is also common. In this sense, it is understood that there are elements that can be modified for a more cooperative management.